2001
DOI: 10.1182/blood.v98.1.231
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of methotrexate: toxicity among marrow transplantation patients varies with the methylenetetrahydrofolate reductase C677T polymorphism

Abstract: This study investigated whether a polymorphism in the 5,10-methylenetetrahydrofolate reductase (MTHFR) gene (C677T) modifies responses to methotrexate (MTX) in patients undergoing bone marrow transplantation. About 10% to 12% of the population carry the MTHFR TT genotype (enzyme activity, 30% of wild type [CC]). Patients (n ‫؍‬ 220) with chronic myelogenous leukemia underwent marrow allografts and were given a short course of MTX. MTX toxicity measures included the oral mucositis index (OMI), speed of engraftm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
126
2
10

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(141 citation statements)
references
References 20 publications
3
126
2
10
Order By: Relevance
“…For example, MTHFR TT677 patients with CML who received MTX for the prevention of a graft-versus-host disease, experienced higher toxicity, as documented by increased oral mucositis and delayed platelet recovery. 15 Increased MTX toxicity was also noted in ovarian cancer patients with the TT677 genotype, 28 and in patients with rheumatoid arthritis who were carriers of the T677A1298 haplotype. 16 MTX-associated effects observed in these studies were suggested to arise due to low 5-methyl-THF levels associated with the T677 variant.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, MTHFR TT677 patients with CML who received MTX for the prevention of a graft-versus-host disease, experienced higher toxicity, as documented by increased oral mucositis and delayed platelet recovery. 15 Increased MTX toxicity was also noted in ovarian cancer patients with the TT677 genotype, 28 and in patients with rheumatoid arthritis who were carriers of the T677A1298 haplotype. 16 MTX-associated effects observed in these studies were suggested to arise due to low 5-methyl-THF levels associated with the T677 variant.…”
Section: Discussionmentioning
confidence: 98%
“…11,12 Recently, the potential role of these polymorphisms in response to MTX treatment has been addressed in several studies. [13][14][15][16] Higher in vitro MTX sensitivity of a patient's lymphoblasts with the TT677 genotype has been shown. 13 Likewise, among adult acute lymphoblastic leukemia (ALL) and chronic myelogenic leukemia (CML) patients receiving MTX, higher drug toxicity was observed in TT677 homozygotes as compared to individuals with other MTHFR genotypes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This SNP has been associated with increased oral mucositis and delayed platelet recovery in patients undergoing allogeneic HSCT for chronic myelogenous leukemia who received cyclophosphamide/TBI or busulfan/cyclophosphamide conditioning and MTX prophylaxis for GVHD. 50 Controlling for other risk factors, patients with lower MTHFR activity and the TT genotype had significantly higher mean mucositis scores. These results were confirmed by Robien et al 51 after excluding patients who required leucovorin rescue and adjusting for pretransplant vitamin use.…”
Section: Renal Failurementioning
confidence: 99%
“…For patients with the homozygous TT variant (lower enzyme activity), there was a significant increase in mucositis and time to platelet engraftment. 25 This same cohort was slightly expanded and underwent further analyses of an additional MTHFR polymorphism (A1298C) as well as two polymorphisms in the thymidylate synthase gene. In an analysis of combined genotypes, the MTHFR A1298C polymorphism with a wild-type MTHFR 677CC genotype showed no changes in the risk of mucositis while the MTHFR C677T genotype persisted as a risk factor for mucositis.…”
Section: Discussionmentioning
confidence: 99%